1999
DOI: 10.1111/j.2042-3306.1999.tb05231.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measures of bone shape in young Thoroughbreds during training for racing

Abstract: SummaryThe aim of this study was to determine if changes in the shape of the third metacarpal bone (MC3) during the first preparation for racing in young Thoroughbred racehorses could be measured radiographically. Lateral radiographs of each MC3 were taken when the horses commenced training, every 2 weeks for 10 weeks, and again at 6 months after the start of training. The width of the dorsal cortex (DC), palmar cortex (PC), and medulla (M) were measured at a position 2.5 cm distal to the nutrient foramen befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Similar structural adaptations have been observed in response to race training for the third metacarpal bone of Thoroughbred racehorses (Nunamaker et al . 1989; Davies et al . 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Similar structural adaptations have been observed in response to race training for the third metacarpal bone of Thoroughbred racehorses (Nunamaker et al . 1989; Davies et al . 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the variation in body size and different types of activity between the groups might reasonably highlight possible effects of these factors on the carpal bone shape. In the metacarpal bone for example, it was found that exercise caused changes in dorsopalmar (Davies et al., 1999) and lateromedial (Hiney et al., 2004) diameter. In respect to the height of the carpal bones, the differences between the two groups were only significant in the radial and third carpal bones.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly BV/TV of the distal metacarpus was associated with any fatal injury suggesting that this is a more sensitive measure of skeletal overload than midshaft shape. Changes in the midshaft are probably more a reflection of dorsal metacarpal disease than developing condylar fractures .…”
Section: Discussionmentioning
confidence: 99%